University elective course 'Digital and natural science methods in archaeology' - Vodolazhskaya L.N. (Cultural Heritage and Modern Technologies, 2024)
The article discusses a new transdisciplinary course ‘Digital and natural scientific methods in archaeology’, developed at the Department of Informatics of the Physical-Technical Institute of the Crimean Federal University and introduced into the educational process in the 2022/2023 academic year. Its relevance is shown, as well as its connection with one of the priority sectors of the economy - the tourism industry and related areas. The article describes the structure of the course, its content and topics. The importance of mastering this optional course for more effective teaching of students in the humanities and the introduction of digital methods in archaeological and cultural studies is noted. It is emphasized that the program of the interdisciplinary course was developed by an employee who has a second higher education - an historical/archaeological education, as well as experience in museums and archaeological expeditions, which made it possible to develop a course program that is maximally focused on actual practical tasks.